2023
DOI: 10.1021/acsabm.2c01030
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin Stabilized Nanoceria for Hydrolytic Cleavage of Paraoxon in Aqueous and Cationic Micellar Media

Abstract: Beta-cyclodextrin (β-CD) stabilized cerium oxide nanoparticles (β-CD@CeO 2 NPs) were synthesized through a hydrothermal route. The electronic properties, surface functional group, surface composition, size, and morphologies of the as-synthesized β-CD@CeO 2 NPs were characterized using UV−visible spectroscopy, FTIR analysis, high resolution X-ray photoelectron spectroscopy (HRXPS), high resolution transmission electron microscopy (HRTEM), and field emission scanning electron microscopy (FESEM). The pH-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Our study showed the opposite, with a higher degradation activity of NPs in alkaline conditions. These results are in agreement with the one of Janos et al, Zhan et al, and Miri et al The higher efficiency may be related to the acid–base properties of 4-nitrophenol making it a better leaving group at higher pH or to a change in the surface of CeO 2 NPs. Vincent et al have explained that CeO 2 NPs in suspension can adsorb protons (H + ions) or OH – ions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study showed the opposite, with a higher degradation activity of NPs in alkaline conditions. These results are in agreement with the one of Janos et al, Zhan et al, and Miri et al The higher efficiency may be related to the acid–base properties of 4-nitrophenol making it a better leaving group at higher pH or to a change in the surface of CeO 2 NPs. Vincent et al have explained that CeO 2 NPs in suspension can adsorb protons (H + ions) or OH – ions.…”
Section: Discussionsupporting
confidence: 93%
“…Miri et al have demonstrated that the OH – ions adsorbed on the CeO 2 NPs surface are very strong nucleophiles that attack the phosphorus center of POX. The entity responsible of the degradation of POX is indeed the OH – bound on the surface of the NP and not other nucleophiles as HO – or H 2 O present in solution . Taken together, this information explains why at a basic pH the degradation of POX is increased.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, enzymes, being biocatalysts with protein-based composition and various specific activities, can be substituted with CeO 2 nanoparticles, as proposed by Xiao et al [202]. CeO 2 nanoparticles have potential applications in oxidative nanozymes, environmental [203], medical [204], and bactericide [205] applications.…”
Section: Strong Oxidantmentioning
confidence: 99%
“…On the other hand, nanocubes (5–60 nm), dominated by (100) crystal faces, showed only marginal activity. Alternatively, water-soluble CeO 2 nanoparticles hydrolyzed diethyl 4-nitrophenyl phosphate without general-base catalyst [ 131 ]. To an aqueous solution of Ce(NO 3 ) 3 , β-cyclodextrin was added, and then NaOH solution was introduced.…”
Section: Catalysis Of Ceo 2 (Ceria) For the Hydrol...mentioning
confidence: 99%